Molecular Identification of Avian Influenza A Virus in House Flies (Musca domestica Linnaeus) Collected from Different Poultry Farms in Indonesia - Hastari Wuryastuti; R. Wasito (Jurnal Sain Veteriner, 2013)
To date, the outbreaks of avian influenza viruses (AIV) in Indonesia are still highly lethal to poultry. The AIV in Indonesia has also infected to humans and make the AIV situation is more serious than in other Asian countries. It is believed that the most likely source of AIV H5N1 infection is the chicken. Since the fly is a wellknown cosmopolitan pest of the poultry farm and home as well as a valuable alternative vehicle of diseasecausing microorganisms, the possibility of the presence of AIV H5N1 in the house flies (Musca domestica L) was investigated with the overall aim of determining the possible mechanical and/or biological vector of avian influenza virus. The RT-PCR was performed on abdominal parts of the house flies. The present of influenza A H5N1 was confirmed by RT-PCR with primers specific for NP, H5 and N1 genes. In the present study, all flies molecularly analyzed have gene expression of avian influenza virus of subtype H5N1. The RT-PCR detects AIV H5N1 isolates of the houseflies samples of the different geographic origin (Sidrap, South Sulawesi, Blitar and Malang, East Java and Karanganyar, Central Java). All those provinces had the different history of the AIV H5N1 outbreaks. On the other hand, results of the RT-PCR assay on the flies collected from Tuban, East Java in the area where never had any AIV outbreaks considered to be negative AIV H5N1 gene expression. Our findings suggest that, in Indonesia, houseflies may be important in the transmission of AIV H5N1. Further studies, however, still need to be done to decide whether houseflies is a mechanical and/or biological vector of avian influenza virus H5N1.